‘Can you play that?’: Moll's Urban Witchcraft in The Roaring Girl - Loeb, Andrew (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
This essay explores the migration of witchcraft language from the rural environs in which we typically find it to the urban space of London in Dekker and Middleton’s The Roaring Girl. The play’s characters repeatedly turn to the language of witchcraft to describe Moll’s disruptive presence in the play, a rhetorical strategy that I argue seeks to fix Moll in place in response to her unruly movement within the social, spatial, and acoustic horizons of the city, and to ostracize her from London by reimagining her as a figure that only makes sense in the rural environs beyond its walls.